Predictability of Extreme Returns in the Turkish Stock Market - Ali, Syed Riaz Mahmood; Ahmed, Shaker; Hasan, Mohammad Nurul; Östermark, Ralf (Taylor & Francis, 2021)
In this paper, we show that extreme returns can predict future returns in the Turkish stock market. We find that extreme return (high MAX) generating stocks show a lower performance in the next month in this market. More explicitly, there is a strong negative relationship between the firm’s maximum (MAX) daily returns over the previous month and its succeeding stock returns. Our results are robust in both firm-level cross-sectional, and portfolio-level analysis.
Keywords: extreme return; max effect; Turkey; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|